Determinan Unified Theory of Acceptance and Use of Technology Terhadap Minat Adopsi Mobile Banking pada Mahasiswa di Kota Samarinda - Agelli Tri Putri; Rizky Yudaruddin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This This study aims to examine the influence of Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions on mobile banking adoption intention among university students in Samarinda. This study employed a quantitative research approach. The sampling technique used was non-probability sampling, specifically purposive sampling. Data were collected by distributing questionnaires to 100 students at Universitas Mulawarman who had experience using mobile banking services. Data were analyzed using Variance-Based Structural Equation Modeling (SEM), namely Partial Least Squares (PLS), with the assistance of SmartPLS software. The results indicate that Performance Expectancy has a positive and significant effect on mobile banking adoption intention. Effort Expectancy has a positive but insignificant effect on mobile banking adoption intention. Social Influence also has a positive but insignificant effect on mobile banking adoption intention. Meanwhile, Facilitating Conditions have a positive and significant effect on mobile banking adoption intention. These findings suggest that the perceived usefulness of mobile banking and the availability of supporting resources are the primary factors influencing students' intention to adopt mobile banking, whereas perceived ease of use and social influence do not significantly affect their adoption intention.